Comparison of single- and multiple-person mercury exposures. Issue 5 (3rd September 2017) - Forrester, Mathias B.
ABSTRACT: Elemental and organic mercury are extremely toxic. All mercury exposures reported to Texas poison centers during 2000–2013 were identified. The cases were divided into multiple- and single-person exposure groups and compared, including identification of statistically significant differences (SSDs). There were 6, 521 single-person exposures and 214 multiple-person incidents involving 734 total persons; 45% and 27% of the multiple- and single-person exposures, respectively, involved patients aged 6–19 years (SSD). The multiple- and single-person exposures were, respectively, 87% vs 98% unintentional (SSD). The most frequent routes of multiple- and single-person exposures, respectively, involved ingestion (23% vs 72%, SSD), dermal (52% vs 23%, SSD), and inhalation (43% vs 5%, SSD). The most common site for multiple- and single-person exposures was the patient's own residence (56% vs 91%, respectively, SSD). Multiple-person mercury exposures are more likely to involve school-age children. A greater proportion of multiple-person exposures was intentional, involved dermal and inhalation routes, and occurred at school.